The relationship between state of mental health and factors affecting mental health on academic performance / Mohd Zarir Yusoff, Muhammad Ammar Shafi and Nur Fareesa Ismail - Yusoff, Mohd Zarir; Shafi, Muhammad Ammar; Ismail, Nur Fareesa (Universiti Teknologi MARA, Negeri Sembilan, 2023)
In March 2020, all educational institutions such as schools and universities were closed due to curb the spread of COVID-19 in Malaysia. Online learning has led to mental health issues among students that can affect their abilities and their academic performance. The aim of this study is to identify the relationship between mental health and academic performance among third-year students at UTHM. This study is using quantitative methods and questionnaires were distributed in order to collect the data. The study will develop valid and reliable scales in order to measure the factors in the relationship between mental health issues and academic performance among third-year students in UTHM. This study can provide many benefits both outside and within the institution, especially among students and universities. the sample size for this study is 375 respondents from undergraduate students in UTHM. The response rate for this research is 23.46%. All the data was collected and analyzed by using the Statistical Package for Science Social (SPSS). Based on the descriptive analysis results, the level of feeling sad and depressed of students is the lowest and the nominal factors that affect students' mental health are needed to do a part-time job due to financial difficulties of the family members. The level of mental health has no significant relationship with the effect on academic performance. While the factors that affect their mental health have a significant relationship with the effect on their academic performance. This research might be useful for future studies which will be focus on identifying the antecedent of the mental health and prevention methods solve the matter. The limitation of this research is the management of time and develop more relevant and valid questionnaires.